KEPENTINGAN INDONESIA DALAM MENGIMPOR GULA DARI THAILAND TAHUN 2018-2022 - Yasfa, M. Farhan; ', Pazli (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2024)
This research discusses Indonesia's interest in importing sugar from Thailand in the period 2018 to 2022. Indonesia imports sugar with the aim of meeting the national sugar consumption needs which continue to increase while domestic sugar production is not yet able to meet demand. Thailand is one of the sugar importing countries for Indonesia because sugar from Thailand is famous for its high quality, optimal agricultural conditions and sophisticated processing technology. The research method used is a qualitative method with data collection techniques through literature studies sourced from several books, journals, articles and websites. This research uses the perspective of Liberalism and International Trade theory The research results show that Indonesia's interest in importing sugar from Thailand is due to economic and political interests. Indonesia's domestic sugar production faces various challenges which result in an inability to meet the increasing domestic demand for sugar. By importing sugar from Thailand, Indonesia can maintain price stability and sugar availability in the domestic market. Apart from economic interests, Indonesia's political interests in importing sugar are to maintain and strengthen bilateral relations and regional economic stability, supporting Indonesia's strategic goals with Thailand within the framework of ASEAN cooperation. Keywords: Sugar, Indonesia, Imports, Importance, Thailand